ماهية أفعال المطاوعة وسلوكها النحويّ - فرحت, هيثم (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The primary aim of the present paper is to investigate the syntactic distribution of middle verbs in English. Middle formation seems to involve demotion of the external argument and promotion of the internal argument to the grammatical subject position, as is the case in passivisation. This paper is organized as follows. In section 1, we offer a definition of the term “middle verb” and present some of its distinguishing features. In section 2, we look into the question of whether or not middles involve 0-roles. In section 3, we shed some light on the nature of the empty category and the syntactic position external arguments fill in middles. Then in section 4, we examine whether middles are the end-product of a movement operation. Finally, in section 5, we bring the paper to a close by concluding remarks to the effect that the empty external 0-roles in middles syntactically emerge as PROs. يكمن الهدف الرئيس للورقة الحالية في سبر أغوار السلوك النحوي لأفعال المطاوعة في الإنكليزية، إذ تتجلى صياغتها في التقليل من شأن مركب اسمي خارجي وإبراز مركب اسمي داخلي يقوم مقام الفاعل، كما هي الحال في المبني للمجهول. ويتم بناء هذه الورقة على النحو الآتي: نقدم في القسم الأول تعريفاً لمصطلح "فعل المطاوعة" ونبرز بعضاً من خصائصه المميِّزة. ونتطرق في القسم الثاني إلى مسألة احتواء أفعال المطاوعة لأدوار محورية أو انتفائها. أما في القسم الثالث، فنقوم بتسليط الضوء على طبيعة الصيغة الصامتة في تراكيب أفعال المطاوعة والموقع النحوي الذي تشغله المركبات الاسمية الخارجية. ونبحث في القسم الرابع إمكانية عدّ تراكيب أفعال المطاوعة نتاجاً لعملية نقل. وأخيراً، نطوي هذه الورقة بعبارات ختامية مفادها أن الأدوار المحورية الخارجية الصامتة في تراكيب أفعال المطاوعة تبرز بوصفها حالات من "ضم الكبير".